Cocaine Induced Pleural and Pericardial Effusion Syndrome - Shehabaldin Alqalyoobi; Omkar Vaidya; Al-Ma’Mon Abu Ghanimah; Ahmed Elkhanany; Ashraf Gohar (Case Reports in Pulmonology)
A 42-year-old African American female with chronic cocaine use for 20 years, presented with two-day history of exertional shortness of breath and pleuritic chest pain. She was admitted three years back with acute kidney injury and skin rashes. At that time, skin biopsy was consistent with leukocytoclastic vasculitis and renal biopsy revealed proliferative glomerulonephritis. She responded to oral prednisone and mycophenolate with complete recovery of her kidney functions. Skin rash was waxing and waning over the last two years. On the second admission, patient was found to have large pleural effusion on computerized tomography scan and pericardial effusion on echocardiogram as shown in the figures. Pleural fluid analysis was exudative. Her serology was negative for ANA (antineutrophilic antibody) and anti-dsDNA (double stranded DNA). Complements levels were normal. She had positive low titers of ANCA levels. The patient was started on a course of prednisone for 6 months. Her pleural and pericardial effusion resolved completely on follow-up imaging with computerized tomography scan and echocardiogram. This case is unique since the pericardial and pleural effusions developed without any other etiology in the setting of cocaine; hence, we describe this clinical syndrome as cocaine induced pleural and pericardial effusions syndrome (CIPP).